Exploring Democratic Principles in Social Studies Education: A Student Perspective in Higher Education - Sari, Ratih Karunia (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This research aims to explore the perception of PGSD students regarding the application of democratic principles in social studies courses in higher education. The study uses a qualitative approach with in-depth interviews, involving 15 students from Nugroho Doctoral University. The findings show that most students feel empowered and engage more actively in democracy-based learning. The open discussion spaces allow them to express their opinions and collaborate on learning topics. However, challenges such as the dominance of lecturers in discussions, lack of student confidence to speak up, and inefficient time management in discussions were identified. These challenges hinder the full potential of democratic learning. The implications of these findings emphasize the need for a balance of roles between lecturers and students, reducing lecturer dominance, and improving discussion time management to ensure efficient and directed learning. This research contributes to the development of more participatory and inclusive learning models, enhancing the quality of education in higher education, especially in social studies courses. Furthermore, the study provides insights into the challenges and benefits of democratic principles in education and suggests strategies for improving student participation and lecturer facilitation, contributing to the broader discourse on participatory pedagogy.